PROTOTYPE ALAT NOTIFIKASI KETINGGIAN AIR DAN PEMUNGUTAN SAMPAH OTOMATIS ANTISIPASI BANJIR DENGAN SENSOR ULTRASONIK WITH GLOBAL SYSTEM FOR MOBILE COMMUNICATIONS - Agung Kharisma Hidayah; Ririn Apriza; Rozali Toyib (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2022)
Governor Rohidin requested that the Bengkulu City Government should tighten housing development permits so that green open spaces are still available, improve the Watershed (DAS) with its ecosystem and routinely clean up garbage - to the point of blocking drainage in the city and floodgates entering from the river. which entered the city of Bengkulu which caused flooding due to rain upstream and the absence of early warning when the water reached the city of Bengkulu and the amount of garbage that clogs the floodgates further aggravated the situation. The prototype of the water level notification tool system for mobile communication that allows early notification when the floodgates increase in height so that people can be alert and also designed an automatic garbage collection tool with ultrasonic sensors that can detect garbage approaching at the water gate at a predetermined distance. The test results have notifications that have been carried out, can send SMS automatically to the destination number and issue an alarm then emit a speaker sound as a sign of the presence of water levels. Objects That Can Be Picked Up By The Conveyor In The Form Of Light Garbage That Is On The Surface Of The Water. Robot Information System in the form of an LCD that will display the results of the water level.